THE PROBLEM AND IMPROVEMENT OF THE THEORETICAL FOUNDATIONS OF PHYSICAL EDUCATION IN SCHOOLS OF GENERAL SECONDARY EDUCATION (Conferencea, 2023)
The article discusses the improvement of the theoretical foundations of physical education in schools of general secondary education.